Utility of platelet rich fibrin gel therapy in nonhealing ulcer secondary to ecthyma gangrenosum. Issue 3 (16th April 2019) - Rajan M, Bandhala; Singh, Saurabh
Abstract: Platelet rich fibrin (PRF) gel is a new second generation platelet concentrate, which has been widely used in various dermatological conditions such as nonhealing diabetic foot ulcers, venous ulcers, and trophic ulcers in leprosy. In this case report, we present a patient with nonhealing ulcer secondary to ecthyma gangrenosum, who showed dramatic response with PRF gel. This case suggests a role of PRF gel in nonhealing ulcers of infectious etiology which has not been described in English language literature. Considering previous literature and our case, it may be concluded that PRF gel may be utilized as an effective alternative for nonhealing ulcers of nonneoplastic etiology.